Efficiency in reading / Fatihah Mohd Sebri - Mohd Sebri, Fatihah (Faculty of Information Management, 2015)
Information is knowledge that we acquired everyday through experience or study and information also is the act of informing or the condition of being informing by the others in our surrounding. Besides, information helps us in doing our daily activity very well. This information is important to every people because information guide them in all situations that they do every day. As example a student need information to complete their assignment and to be successful in their studies. All the information need to be organized and processed to convey the understanding experiences, accumulated learning and expertise. People must gain information in all condition way and need to organize that information very well. In the process to get the right and more information in our life, we need to read efficiently in all types of book, article, magazine, newspaper and many others sources of reading that can give us information. Efficiency in reading is referring to the ability of once reading. Thus, efficiency in reading can be define as achieving the great speed in reading and high accuracy in understanding of written material and speed in reading can differ as how much word can be read perminute and how many questions can be answer correctly. In efficiency in reading I would explain about efficiency of reading strategy and the benefit that will can get from reading with efficient.